PENGARUH PENGGUNAAN METODE PEMBELAJARAN THINK TALK WRITE (TTW) TERHADAP KEMAMPUAN BERPIKIR KREATIF DAN AKTIVITAS SISWA - Wirda Wirda (JURNAL TEMATIK, 2019)
The purpose of this study was to determine the effect of the use of think talk write learning methods on the ability to think creatively and student activities in Civics Education in SDNegeri No.060856 Medan City. This type of research is quasiexperimental. The population of this research is class V students consisting of 2 classes with 60 students. Determination of the sample with a total sampling technique that is the whole class V-A and V-B students with a total of 60 people. Research instruments to measure creative thinking skills are used tests and observation sheets for student learning activities. Data analysis techniques used a comparison of the average of two sample groups. The results of the study are that there is an influence of TTW and conventional learning methods on students' creative thinking abilities. This influence is evidenced by an increase in students' creative thinking skills during learning activities that is students dare to express new ideas, like to think of different ways, show desires through the activities that they try themselves, like to demonstrate new things, like to do things that are not known beforehand, and students dare to reveal the answers even though they do not know the truth of the answers. So there is an influence of TTW and conventional learning methods on student learning activities.